Identification of aldehyde dehydrogenase 1A1 modulators using virtual screening. (June 2013) - Kotraiah, Vinayaka; Pallares, Diego; Toema, Deanna; Kong, Dehe; Beausoleil, Eric
<x xml:space="preserve">Abstract</x> The highly similar aldehyde dehydrogenase isozymes (ALDH1A1 and ALDH2) have been implicated in the metabolism of toxic biogenic aldehydes such as 3, 4-dihydroxyphenylacetaldehyde (DOPAL) and 4-hydroxy-2E-nonenal. We report the down-regulation of ALDH1A1 mRNA found in substantia nigra tissue of human Parkinson's disease (PD) samples using the Genome-Wide SpliceArray™ (GWSA™) technology. Since DOPAL can rapidly inactivate ALDH1A1 in vitro, we set up a DOPAL-induced ALDH1A1 inactivation assay and used this assay to demonstrate that Alda-1, a compound originally identified as an activator of ALDH2, can also activate ALDH1A1. We carried out a virtual screening of 19, 943 compounds and the top 21 hits from this screen were tested in the DOPAL inactivation assay with ALDH1A1 which led to identification of an activator as well as two inhibitors among these hits. These findings represent an attractive starting point for developing higher potency activator compounds that may have utility in restoring the metabolism of DOPAL in PD.